THE DEVELOPMENT OF AN ACEH CULTURE-BASED ETHNOMATHEMATICS MODULE FOR ELEMENTARY SCHOOL - Zikra Hayati; Nida Jarmita; Herawati Herawati; Nurmalina Nurmalina; Raudhahtun Nisa (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2025)
This study focuses on the development of an ethnomathematics module incorporating Aceh culture for Grade IV students at SDN 58 Banda Aceh. The aim is to create a culturally relevant learning resource that improves students' understanding of mathematical concepts, particularly quadrilaterals. Using the Research and Development (R&D) method with the ADDIE model, the study included a needs analysis, expert validation, and practicality assessments. The needs analysis revealed that existing materials lacked contextual relevance for students. The module received positive feedback from experts, with media expert validation scoring 98.3% and content expert validation at 90.55%, both categorized as "very feasible." Practicality tests with teachers and students showed scores of 93% and 91.8%, respectively, indicating the module’s high practicality. The findings suggest that the Aceh culture-based ethnomathematics module is both feasible and practical for use in enhancing students' learning experiences